1996
DOI: 10.1116/1.580288
|View full text |Cite
|
Sign up to set email alerts
|

Electron-induced surface chemistry: Production and characterization of NH2 and NH species on Pt(111)

Abstract: A lowenergy electron diffraction data acquisition system for very low electron doses based upon a slow scan charge coupled device camera Rev.Irradiating molecularly adsorbed NH 3 with controlled fluences of 50 eV electrons on Pt͑111͒ at 100 K leads to NH 2 , NH, and H species. Temperature programmed desorption shows dihydrogen desorption, confirming electron induced decomposition of ammonia, and a new NH 3 desorption peak ͑210 K͒ attributed to hydrogenation of NH 2 . High resolution electron energy loss spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
44
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 11 publications
12
44
1
Order By: Relevance
“…N ? H. This is significantly larger than the corresponding barriers on Pt(111) (32 kcal/mol) and Pt(100) (24 kcal/mol) [48]. In light of the relatively high reaction barrier and the endothermicity of this reaction, it is thus expected that the dissociation of NH fragment on SiCNT is unfavorable both kinetically and thermodynamically, which is consistent with the other theoretical results [36][37][38].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…N ? H. This is significantly larger than the corresponding barriers on Pt(111) (32 kcal/mol) and Pt(100) (24 kcal/mol) [48]. In light of the relatively high reaction barrier and the endothermicity of this reaction, it is thus expected that the dissociation of NH fragment on SiCNT is unfavorable both kinetically and thermodynamically, which is consistent with the other theoretical results [36][37][38].…”
Section: Resultssupporting
confidence: 75%
“…All of these NH x species have been experimentally observed on metal surface using surface sensitive techniques such as high resolution electron energy loss spectroscopy (HREELS) [48,49]. A recent study [36] suggests that the successive dehydrogenation of ammonia over Fe(100) surface is not a quick kinetic process, but rather sizeable activation energy barriers exist along the reaction pathway.…”
Section: Resultsmentioning
confidence: 98%
“…According to Sun et al [34], the peak at lower binding energy of 398.0 eV is assigned to NH and the peak at higher binding energy to NH 2 species. The BE peaks representing NO (a) [35,36], NH 3 [34,37], N 2 [38], N 2 O [39], and atomic nitrogen [40] were not observed in our XP spectra.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%
“…Unfortunately, not much XPS data on NH x fragments with clear assignment of the peak positions were available in the literature (Table 2). Sun et al [31] and Weststrate et al [32] reported the BE of 397.5 eV and 397.6 eV for the NH ads species on the Pt(1 1 1) and Ir(1 1 0) surfaces, respectively. Assuming the correctness of the above outlined BE assignments, we suggested that the NH ads species was present on the Ru(0 0 0 1) surface during the steadystate catalytic reduction of nitric oxide with excess hydrogen.…”
Section: Temperature (K)mentioning
confidence: 99%
“…The rule of thumb is that the DBE between different NH x,ads species is approximately 1 eV (see for instance Refs. [31,32] and Table 2). From this point of view, the DBE between NH ads (397.4 eV) and N ads (397.1 eV), which is only 0.3 eV, does not look very convincing.…”
Section: No + H 2 Reactionmentioning
confidence: 99%